ANALISIS PENGENDALIAN KUALITAS PRODUK KAIN PRINTING MENGGUNAKAN PENDEKATAN STATISTICAL QUALITY CONTROL - Pitasari, Dewi Nur; Kurniani, Kurniani -; Hidayat, Yusmar Ardhi (Admisi dan Bisnis, 2018)
PT Sri Rejeki Isman Tbk. is a manufacturing company producing textiles and garment which has commited to provide high-quality products for its consumers. The company strives to improve its product quality and reduce theproduct defectlevel by setting out defect level standard by 10% of total production. However, in the implementation, the reject number occurred still exceeds more than the specified defect product tolerance limit i.e. 10%. This study aimed to analyze the quality control implementation which has implemented by PT Sri Rejeki Isman Tbk, to find out the factors resulting in reject product and to provide suggestion on quality improvement that can be applied by the company. Quality control analysis is done using statistical tools contained in Statistical Quality Control (SQC) such as check sheet, histogram, c-chart, Pareto diagram and fishbone chart.C chart analysis result showed that there were still 12 points passed the upper limit, indicating that quality control process in the company needs further improvement. Based on Pareto diagram, it could be seen that the dominant defects were crease mark (34,1%), spotting (27,2%), shading (22,6%) and miss print (16,1%). According to fishbone analysis, the main factors causing printing fabric defect are machine, man, material and method. The company could conduct preventive and corrective actions to decrease defect level by regenerating defective machine component, conducting employee training and enhancing supervision to the employee performance and production result of each process.